RANCANG BANGUN APLIKASI MOBILE SISKA BERBASIS ANDROID - Ceryna Dewi, Ni Kadek; Anandita, Ida Bagus Gede; Atmaja, Ketut Jaya; Aditama, Putu Wirayudi (LPPM STMIK STIKOM Indonesia, 2018)
SISKA is an Academic Information System at Ganesha University of Education (UNDIKSHA) used for TESIS process. Starting from proposal submission, proposal seminar, pre thesis exam and thesis exam. So far the running application is still in web form. With so rapid development of Android-based applications, it will be made SISKA Android-based applications that will certainly make it easier for students and lecturers to access this application via Smartphone. In the development of this application will be used Eclipse commonly used for software development. Web-based SISKA application development into Android-based SISKA application provides a new look that is more user friendly, easy to use, and easy to access using smartphone